PWE-243 Narcotic bowel syndrome: a local experience of the hidden burden. (22nd June 2015) - Johnson, MW; Prouse, T
Abstract : Introduction: The use of prescribed narcotic drugs has escalated throughout UK. There are 220, 000 people within the Luton CCG catchment area and between June–November 2014, 32, 956 prescriptions had been provided for strong opioid therapy. Not only is this a costly unchecked market, but much of this is taken for abdominal pain. Narcotic Bowel Syndrome (NBS) is under recognised and believed to be increasing in prevalence worldwide. NBS is a subset of opioid bowel dysfunction that is characterised by chronic or frequently recurring abdominal pain that worsens with continued or escalating dosages of narcotics. We attempted to assess the demand placed on the NHS system by NBS patients. Method: In 2014 we started to collect the names of patients seen in gastroenterology clinics or during hospital admission where the clinician felt the patient was suffering from NBS. This was either thought to be the main cause or contributing factor to their symptomatology. A 12 year retrospective review was then made using the hospital coding system to assess the demand made by these patients on the Luton and Dunstable University Hospital through either outpatient clinic visits and/or hospital admissions. Results: A database collated the names of 41 patients with NBS. Between January 2000 and December 2014 this cohort of patients have had a total of 660 hospital admissions and 1407 outpatient appointments. In that 15 year time period, the patients had an average of 16 hospital admissions (1.1 per year) each, and 34.3 outpatient clinic appointments each (2.3 per year). During this review period 2 patients died; one 46y old male died from a definite overdose, and one 33y old died from a probable overdose. Conclusion: NBS is a poorly recognised condition that places a huge demand on the NHS system with regards to time, resources and finances. Early recognition could prevent a costly and potentially fatal pathway of deterioration. Disclosure of interest: None Declared.